Mechanisms Underlying Mu Opioid Receptor Effects on Parallel Fiber-Purkinje Cell Synaptic Transmission in Mouse Cerebellar Cortex - Yang, Yi; Bai, Jin; Sun, Jia-yue; Ye, Ting; Zhang, Lu; Wu, Feng-ying; Nan, Jun; Lan, Yan (Frontiers in Synaptic Neuroscience, 2022)
μ-opioid receptors (MOR) are widely expressed in the brain, varying in density in different areas. Activation of MORs underlies analgesia, euphoria, but may lead to tolerance, dependence, and ultimately opioid addiction. The Purkinje cell (PC) is the only efferent neuron in the cerebellar cortex and receives glutamatergic synaptic inputs from the parallel fibers formed by the axons of granule cells. Studies have shown that MORs are expressed during the development of cerebellar cells. However, the distribution of MOR and their effects on PF-PC synaptic transmission remain unclear. To examine these questions, we used whole-cell patch clamp recordings and pharmacological methods to determine the effects and mechanisms of MOR activation on synaptic transmission at PF-PC synapses. The MOR-selective agonist DAMGO significantly reduced the amplitude and area under the curve (AUC) of PF-PC evoked (e) EPSCs, and increased the paired-pulse ratio (PPR).DAMGO-induced inhibitory effects on PF-PC eEPSCs and PPR were abolished by MOR specific blocker CTOP. Further, DAMGO significantly reduced the frequency of PF-PC mEPSCs, but had no obvious effect on their amplitude, suggesting a presynaptic site of action. The DAMGO-induced reduction in the frequency of PF-PC mEPSCs also was blocked by CTOP. A protein kinase A (PKA) inhibitor PKI added in the pipette solution did not affect the inhibitory effects on PF-PC mEPSCs induced by DAMGO. Both the PKA inhibitor K5720 and MEK inhibitor U0126 in artificial cerebrospinal fluid (ACSF) prevented the inhibitory effects of DAMGO on PF-PC mEPSCs. These findings reveal that MORs are expressed in presynaptic PF axon terminals, where DAMGO can activate presynaptic MORs to inhibit PF-PC synaptic transmission by regulating the release of glutamate. G-protein-dependent cAMP-PKA signaling pathway may be involved in this process.